A systematic review on the connection between learner dropout from online courses and course design qualities - Lencastre, José Alberto (2019)
The problem of high dropout rates in online courses has been widely studied without a clear understanding of what factors contribute to dropout or failure to participate in online course activities (attrition) that are related to course design. To better understand this issue a systematic review of empirical studies was conducted to study what is currently known between online course design with attrition and dropout in online courses. The research strategy identified 1826 studies, of which 35 as empirical studies. After a first critical evaluation by two researchers and a quality assessment by three researchers using two combined versions of the Critical Appraisal Skills Programme, six articles were selected for content analysis. The studies were grouped into eight categories: (i) modality, (ii) objective, (iii) scope, (iv) action, (v) results, (vi) recommendations, (vii) dropout factors, and (viii) strategies to overcome dropout factors. The results showed that there is a relationship between online course design with attrition and dropout. However, focusing only on course design without considering other factors like the student profile, the role of the online trainer, the responsibilities of the training institution, or even the technical support, may be insufficient to reduce dropout rates significantly. We believe this conclusion is as important as understanding the motives and strategies used to overcome attrition and dropout. For online trainers, this systematic review can provide a moment of reflection on their options in designing online courses that anticipate and warn against avoidance.